Pengembangan Media Pembelajaran Berbasis Permainan Katak Lompat Untuk Meningkatkan Kemampuan Literasi Numerasi Siswa Sekolah Dasar - Nadya, Nadya Rahma Juwita; Bramianto Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop a "Jumping Frog" game-based learning medium to improve the numeracy literacy skills of first-grade students at SDN Jayamukti 04. The background for this study is the low level of students' numeracy literacy skills, as shown by observations where around 66.67% of students have difficulty understanding and using numbers in their daily lives. One of the causes is the lack of engaging and effective learning media. The research method used is Research and Development (R&D) with the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The subjects of this study were all 33 first-grade students at SDN Jayamukti 04, with 10 students selected as a sample using a purposive sampling technique. The expert validation results showed that the "Jumping Frog" medium is feasible for use with a percentage of 87%. The responses from teachers and students were also very positive, with percentages of 93% and 97% respectively, indicating that the medium is practical and suitable for use. The effectiveness test using pre-test and post-test showed a significant increase in the average score, from 45.6 to 94 in the limited trial and from 50 to 92 in the large-scale trial. The obtained N-Gain score was 0.8605 or 86.05%, which falls into the "very feasible" and effective category for improving students' numeracy literacy skills.